An alternative method of management for plantations: concentrated spacing towards selected trees - Valdivieso, José Antonio (Bosque (Valdivia), 1990)
A plan for management oriented to middle and small size land owners, is proposed. It consists in allotting a progressive increase of space to a selected group of pruned and eventually fertilized trees. An example is used to characterize the proposed methodology and an analysis based on models currently in use, is done. Finally, some silvicultural considerations are given.